Focused Ultrasound Thalamotomy for the Treatment of Essential Tremor: A 2-Year Outcome Study of Chinese People - Wu, Peihan; Lin, Wei; Li, Kun Hong; Lai, Hui-Chin; Lee, Ming-Tsung; Tsai, Kevin Wen-Kai; Chiu, Pai-Yi; Chang, Wei-Chieh; Wei, Cheng-Yu; Taira, Takaomi (Frontiers in Aging Neuroscience, 2021)
Background: Essential tremor (ET) is a common movement disorder among elderly individuals worldwide and is occasionally associated with a high risk for mild cognitive impairment and dementia. This retrospective study aimed to determine the clinical outcome of unilateral magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy in Chinese patients with ET. Methods: In total, 31 male and 17 female patients with drug-refractory ET were enrolled in this research study from January 2017 to September 2019. The severity of tremor and disability were assessed using the Clinical Rating Scale for Tremor (CRST) within a 2-year follow-up period. Results: The mean age of the participants was 59.14 ± 13.5 years. The mean skull density ratio (SDR) was 0.5 ± 0.1. The mean highest temperature was 57.0 ± 2.4°C. The mean number of sonications was 10.0 ± 2.6. The average maximum energy was 19,710.5 ± 8,624.9 J. The total CRST scores and sub-scores after MRgFUS thalamotomy significantly reduced during each follow-up (p < 0.001). All but four (8.3%) of the patients had reversible adverse events (AEs) after the procedure. Conclusions: MRgFUS had sustained clinical efficacy 2 years after treatment for intractable ET. Only few patients presented with thalamotomy-related AEs including numbness, weakness, and ataxia for an extended period. Most Chinese patients were treated safely and effectively despite their low SDR.